The interaction between OsMADS57 and OsTB1 modulates rice tillering via DWARF14 - Guo, Siyi (Nature Pub. Group, 2013)
Rice tillering is a multigenic trait that influences grain yield, but its regulation molecular module is poorly understood. Here we report that OsMADS57 interacts with OsTB1 (TEOSINTE BRANCHED1) and targets D14 (Dwarf14) to control the outgrowth of axillary buds in rice. An activation-tagged mutant osmads57-1 and OsMADS57-overexpression lines showed increased tillers, whereas OsMADS57 antisense lines had fewer tillers. OsMIR444a-overexpressing lines exhibited suppressed OsMADS57 expression and tillering. Furthermore, osmads57-1 was insensitive to strigolactone treatment to inhibit axillary bud outgrowth, and OsMADS57’s function in tillering was dependent on D14. D14 expression was downregulated in osmads57-1, but upregulated in antisense and OsMIR444a-overexpressing lines. OsMADS57 bound to the CArG motif [C(A/T)TTAAAAAG] in the promoter and directly suppressed D14 expression. Interaction of OsMADS57 with OsTB1 reduced OsMADS57 inhibition of D14 transcription. Therefore, OsMIR444a-regulated OsMADS57, together with OsTB1, target D14 to control tillering. This regulation mechanism could have important application in rice molecular breeding programs focused on high grain yield.